A novel nondestructive testing method for honeycomb structure using acoustic band gap. (1st April 2023) - Yuan, Ye; Liu, Bin; Jia, Han; Zhang, Chi; Zhang, Zhiguo; Wang, Suhao; Yang, Yuzhen; Wang, Xun; Cheng, Xiaobin; Yan, Zhaoli; Yang, Jun
Graphical abstract: Highlights: Dispersion relation in honeycomb structure is calculated more accurately by taking advantage of the space periodicity of the core. A flexural wave band gap is discovered and verified in the intact area of the honeycomb structure. A new nondestructive method for detecting the debonding defect is proposed by using the band gap feature and the corresponding detection device is developed. Abstract: Honeycomb structure is increasingly applied in various fields due to its high strength-to-weight ratios. However, due to the complex wave field in the structure, how to detect the defect accurately and efficiently is always an important problem. In this article, the honeycomb core, instead of being an obstacle to obtain the dispersion characteristic for traditional guided wave method, provides a way to calculate the wave propagation by being taken advantage of its space periodicity. By analyzing, simulating, and experimental testing, it is exhibited that there is a gap in the dispersion relation of the honeycomb structure which caused by the interaction between the local resonant vibration of the skins and the bending vibration of the structure. This gap disappears in the debonding area. Then a nondestructive testing method is proposed to detect the debonding defects based on this feature. The detection results of this proposed method are accord with that of ultrasonic C-scan. The results indicate that this method is suitable for detecting and locating the debonding defects in honeycomb structure with quite high sensitivity and efficiency, and it has a great potential to be widely used in filed test of honeycomb structure for its high feasibility.